Successful Identification of a Neoplastic Tissue Contaminant in Surgical Pathology. Issue 4 (July 2022) - Anderson, Jessica D.; Amin, Mitual B.; Bernacki, Kurt D.
Abstract: Tissue contamination, where extraneous tissue becomes embedded into the paraffin block or fixed onto the slide, is a relatively common quality issue in surgical pathology and can occur at any step between specimen collection by the clinician and slide coverslipping. We report a case of tissue contamination within a paraffin block and describe our subsequent investigation, which was successful in identifying the source of contamination.